Potentially pathogenic autoantibodies associated with epilepsy and encephalitis in children and adults. - Vincent, A; Irani, SR; Lang, B (2011)
Autoantibodies to surface proteins that influence neuronal excitability are increasingly found in different forms of epilepsy or encephalitis in adults, and are also beginning to be identified in children. The conditions are often refractory to traditional antiepileptic drugs. Detection of these antibodies can help to identify forms of epilepsy that may respond to immunotherapies.